COMBINING ABILITY, HETEROSIS AND GENE ACTION USING (LINE × TESTER) ANALYSIS IN CORN - & et al., Abdul-Hamed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was conducted at the Field Crops Research Station of State Board of Agricultural Research at Abu Ghraib in spring 2015. Seven inbred lines of maize (IK8, ZP, W13R, H.S, IK58, ABS 5, ZP607) were used in this study, using Line x Tester analysis, to produced twenty F1 crosses. The parents and crosses were grown in fall season of 2015 using RCBD with three replicates to determine heterosis and general, specific combining ability effects and gene action. Significant differences were found among parental lines and their crosses for all the traits. The result were showed that the cross (IK8×  IK58) gave the highest hybrid vigor in grain yield (42.46%) and produced highest grain yield 214.7 gm.plant-1. The values of specific combining ability variance for all the traits revealed superior to the variance of general combining ability. The dominance genetic variance more important than additive variance, the narrow sense heritability for ear length very low (2.5%), white was highest (36.42%). The result indicate that some inbred lines could be used in a breeding program to develop new versions of high yield hybrids and most studied traits were under dominance and over dominance gene action.